An Approach to Argumentation Schemes that Appeal to Expert Opinion - Budan, Paola D. (2013)
Argumentation is a form of reasoning that deeply resembles the human mechanism for commonsense reasoning. An argumentation scheme is a representational tool for modeling common patterns of reasoning; in particular, it displays the form of an argument by showing how the argument is built using the inferential structures commonly used in everyday discourse. Argument schemes are very useful in contexts such as legal argumentation, scientific argumentation, and especially in Artificial Intelligence applications. One type of argumentation scheme corresponds to appeal to Expert Opinion or Position-to-Know argumentation. Position-to-know reasoning is typically used in an information seeking type of dialogue where one has to depend on a source. Most of such argumentation frameworks are based on Dung’s seminal work characterizing Abstract Argumentation Frameworks. In this work, we introduce a novel framework, called Expert Argumentation Framework (EAF), extending AF with the capability of modeling the quality of expert associated with the arguments that were proposed.